A Cross Sectional Study on the Awareness on the Bio-Medical Waste Management among Medical Students in a Tertiary Care Hospital Chennai (Medico Legal Update, 2020)
Introduction: Biomedical waste (BMW) collection and proper disposal have become a substantial issue forboth the general and the medical community. In the present-day scenario, approximately 25% of biomedicalwaste is found to be hazardous and may affect the health of both general community and medical personnel.Medical students as future professionals are soon going to be an integral part of health care system. Theyshould have proper and sufficient knowledge on BMW management. Moreover, the awareness about variousaspects of BMW management has to be assessed frequently too.Objective: The objective of the study was to assess the awareness of know on biomedical waste managementat tertiary care hospital, (Saveetha Medical College) among medical students.Methodology: This was a cross-sectional study done at Saveetha Medical College and Hospital. A totalof 100 MBBS students were included in the study with their prior consent. A pre tested semi structuredquestionnaires was given to participants. The data was analyzed using software SPSS.Results: 53% were boys and 47% were girl students. Among various questions asked in the Questionnaire,the overall knowledge on the awareness of biomedical waste disposal among medical students was 46.8%.Conclusion: There is a lack of appropriate knowledge about biomedical waste management, awareness andpractices of proper waste disposal. Hence, there is a need of training and programmes regarding health carewaste management.